INTENTION TO PARTICIPATE IN TAX EVASION: A SURVEY OF ACCOUNTING AND NON-ACCOUNTING BACKGROUND EMPLOYEES: Received: 14th February 2023; Revised: 16th June 2023, 22nd June 2023; Accepted: 24th June 2023 - Alwi, Noral Hidayah; Khan, Bibi Nabi Ahmad; Osman, Zahir (PEOPLE: International Journal of Social Sciences, 2023)
Tax evasion is still justified by Malaysian citizens as being tolerable and acceptable, as seen by the greater number of tax evasion cases and rise in unpaid tax figures in the country. This study examines the connection between attitude, perceived behaviour control and subjective norms towards tax evasion behaviour between the accounting and non-accounting background employees. This study adopts a quantitative methodology and based on non-probability sampling of Malaysian individual taxpayers. Google forms were used to collect all the data, then analysed using SPSS 22.0. The results indicate that employees with accounting backgrounds behave differently than those without an accounting background in terms of their aim to evade taxes. All variables show a positive correlation with tax evasion behaviour for employees with non-accounting backgrounds. However, among workers with accounting backgrounds, only subjective norms show a positive impact on tax evasion behaviour. As compares to non-accounting background employees, subjective norms and perceived behavioural control influence the intention to engage in tax evasion. The findings of this study may help employers prevent unintended tax evasion by educating employees on handling their tax returns. Additionally, this outcome will add value to the new knowledge particularly in the literature on tax compliance.